Knowledge and Risk of Osteoporosis among Pre-elderly at Cipacing Village Jatinangor District in 2014 - Ramdhani, Muhammad; Mulyadi, Dicky; Arisanti, Nita (Althea Medical Journa, 2015)
Background: Osteoporosis is a disease characterized by abnormal loss of bone density resulting inbones that are brittle and liable to fracture. Most cases of fracture in the world are due to osteoporosis. InIndonesia, the prevalence of osteopenia (early osteoporosis) and of osteoporosis are relatively high. Oneof the causes of this situation is the low level of public knowledge about how to prevent osteoporosis. Thisstudy was conducted to identify the knowledge and risk of osteoporosis among pre-elderly at CipacingVillage Jatinangor District in 2014.Methods: This descriptive study was conducted at Cipacing Village Jatinangor District to 160 respondentswho were classified as pre-elderly (aged 45-59 years) and assessed on knowledge and risk factors forosteoporosis through questionnaire-guided interviews after the informed consent was obtained.Thecollected data were presented using frequency distribution.Results: A total of 100 respondents (62.5%) had good knowledge about osteoporosis-related information,including definitions, causes, risk factors, signs and symptoms, impacts, and prevention. Most respondents,79 respondents (49.4%), are at risk for osteoporosis.Conclusions: Knowledge of osteoporosis among pre-elderly at Cipacing Village Jatinangor District arelargely classified into âgood knowledgeâ category. [AMJ.2015;2(4):608â14]